First report of Pantoea anthophila causing shoot dieback disease of Ceylon ironwood (Mesua ferrea) in Malaysia - Johari, M. I. H.; Saad, N.; Ismail, S. I.; Jamian, S.; Abdullah, S.; Zulperi, D.; Karam, D. S.; Rajoo, K. S. (The American Phytopathological Society, 2024)
Ceylon ironwood (Mesua ferrea L.) or Penaga lilin is one of Asia’s most popular tropical herbal plants, including in Malaysia (Sharma et al. 2017). The trees are cultivated for their aesthetic value and pharmacological properties, especially as traditional remedies for asthma, dermatopathy, inflammation, and rheumatic conditions (Adib et al. 2019). In August 2022, a disease survey was conducted on Ceylon ironwood trees ranging from 5 to 12 years old in Botanical Park, Putrajaya, Malaysia, with 80% of the 15 trees exhibiting shoot dieback disease. Symptoms include irregular, water-soaked brown lesions on young leaves and shoots, where small lesions coalesced and formed broad necrotic regions, subsequently causing dieback and gradual defoliation. Three infected shoots were collected from each tree, excised into small pieces (10 to 20 mm), immersed in 75% ethanol for 3 min, washed with 2% NaOCl solution for 1 min, and rinsed two times for 1 min in sterilized distilled water. A 10-μl aliquot of the sample suspension was streaked onto nutrient agar and incubated for 24 to 48 h at 35°C. A total of 15 isolates with similar morphology were obtained, and each isolate was restreaked three times to obtain pure colonies that were round and smooth, with irregular edges, and produced yellow pigment in the culture. All isolates were gram-negative, were negative for indole production, and used glucose, maltose, trehalose, sucrose, D-lactose, and pectin. Three representative isolates (C001, C002, and C003) with similar morphology were selected for further characterization. The total genomic DNA of all isolates was extracted from overnight cultures using the Geneaid DNA Isolation Kit (Geneaid Biotech, Taiwan). PCR amplification of 16S rDNA (Zhou et al. 2015) and species-specific infB (Brady et al. 2008) genes was performed, and each of the ∼1,500- and ∼900-bp amplicons was sequenced. BLASTn and phylogenetic analyses revealed that all isolates were 100% identical to Pantoea anthophila (P. anthophila) LGM 2558 strains (accession nos. NR_116749 and NR_116113) for the 16S rDNA gene. They were 99% identical to the P. anthophila CL1 strain (accession no. CP110473) for the infB gene. These sequences were later deposited in GenBank (accession nos. OQ772233, OQ772234, and OQ772235 for the 16S rDNA gene and OQ803527, OQ803528, and OQ803529 for the infB gene). For the pathogenicity test, healthy Ceylon ironwood seedlings’ shoots were inoculated with 10 ml of each isolate suspension (1 × 108 CFU/ml) by spraying the inoculum on the young shoots using a sterilized spray bottle. Control seedlings were inoculated with sterile water. The inoculated shoots were sealed in a plastic bag to maintain the moisture and were kept in a greenhouse with temperatures ranging from 26 to 35°C. The experiments were repeated two times, with three replicates for each treatment. Inoculated shoots showed dieback symptoms such as natural infection, including irregular, water-soaked, and brown lesions on leaves and young shoots 10 days after inoculation. Control seedlings remained asymptomatic. The pathogen was reisolated and identified via sequencing of the 16S rDNA and infB genes, thus fulfilling Koch’s postulates. Previously, P. anthophila has been reported to cause soft rot in wampee plants in China (Zhou et al. 2015) and leaf blight of cotton in Pakistan (Tufail et al. 2020). To our knowledge, this is the first report of P. anthophila causing shoot dieback disease in Ceylon ironwood trees in Malaysia. Plant disease management strategies need to be established to reduce losses because of P. anthophila infection since the pathogen could limit Ceylon ironwood tree production in Malaysia.